Developing a sense of place toolkit: Identifying destination uniqueness. (October 2019) - Jarratt, David; Phelan, Chris; Wain, Jenny; Dale, Sarah
It has long been recognised that the tangible and intangible characteristics that make a location distinctive and memorable contribute significantly to destination image. How this destination feel is communicated has largely been the domain of place branding and destination marketing, which have the potential to miss stakeholder voices. Recently though, practitioners are starting to carefully consider 'sense of place', that is an emotional attachment to place, which is defined more carefully in the literature review of this article, and which corresponds with long-running academic discussions. This paper attempts to identify some of these and bridge the gap between academic theory on sense of place and practice. In the UK, many rural areas are now seeking to operationalise sense of place through toolkit documents that might inform landscape interpretation and destination branding. A scenario echoed internationally, where local distinctiveness features in both rural and urban planning. However, sense of place in a tourism context, and more specifically the development of these toolkits, has received limited academic attention. Hence, this paper presents the case of Morecambe Bay and the development of a dedicated sense of place toolkit. The subsequent case emerges from a collaboration between academics and practitioners and draws on participant observation, semi-structured interviews and document analysis. Specifically, the paper outlines a series of workshop activities developed with destination stakeholders and identifies how these inform subsequent toolkit design. It offers a critical analysis of the benefits and potential pitfalls of employing this approach. This case is of value to academics and destination stakeholders interested in identifying and communicating the uniqueness and emotional tone of the destination. Key lessons and recommendations are identified for those engaging in similar toolkit development initiatives.